(untitled) (International Journal of Clinical Research, 2023)
Background: Uterine leiomyoma (UL) are women’s most common pelvic tumors, benign in nature, growing during reproductive age, and presenting with abnormal uterine bleeding or pelvic pain and pressure. Many risk factors may contribute to UL, such as family history, obesity, and early menarche. Despite the fact that UL symptoms may improve using many medical or surgical treatments, the health-related quality of life (HRQoL) is considerably affected by their presence. Based on all of the above, we conducted this study which is to the best of our knowledge, the first of its kind in Lebanon aiming to assess the risk factors of UL among the Lebanese population and provide an overview of the diagnostic methods, treatment modalities, and HRQoL among patients. Subjects & Methods: This is an epidemiologic case-control retrospective study, of 668 women of reproductive age, of different nationalities living in Lebanon, divided into 167 cases and 501 controls, conducted between January 2016 and February 2018, in Beirut, Lebanon, in Rafic Hariri University Hospital (RHUH) and Makassed General Hospital (MGH), using charts, questionnaires, and telephone calls. The statistical program Statistical Package for the Social Sciences 19 (SPSS-19) was used for data analysis. A multivariate analysis was also done. Two-sided data analysis was employed and statistical significance was considered for a p-value of ≤ 0.05. Results: Risk factors of UL were older age (>40), early menarche, family history, oral contraceptives (OCP) use, high body mass index (BMI) (>29), and chronic diseases. Smoking and sports were protective factors. The highest effectiveness in diagnosis was attributable to pelvic ultrasonography (94.8% of cases), magnetic resonance imaging (MRI) (85.2% of cases), and hysteroscopy (77.8% of cases). Hysterectomy was the most used treatment method (83.8% of cases), followed by hysteroscopy (77.8%) and uterine artery embolization (UAE) (72.7%). Women with leiomyoma reported that their HRQoL is negatively affected by this condition. Conclusion: This study showed many risk factors for UL, and the statistical significance of techniques for their diagnosis and treatment, in order to prevent their complications and decrease their impact on HRQoL.